Assessment of Availability and Reliability of a Textile Manufacturing 4.0 Using Stochastic Models - Silva, Edson Moura; Macieira, Rafael Melo; Araújo, Danilo Ricardo Barbosa de; Andrade, Ermeson Carneiro de (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2024)
The Brazilian apparel industry ranks seventh globally, generating a revenue of USD 10 billion per year. Despite the increasing adoption of Internet of Things (IoT) devices in so-called “Industry 4.0”   manufacturing, accurately estimating crucial indicators such as availability and operational reliability of resources in local garment manufacturing hubs still remains a significant challenge. This assessment can help companies identify areas for improvement and make more informed decisions, resulting in greater competitiveness in the global market. This study proposes an approach based on stochastic Petri nets to model and analyze the failure and repair processes in a 4.0 textile industry within a company from the Agreste Pernambucano garment manufacturing hub. The results suggest that arrangements with resource redundancies can reduce the failure rate by over 60%, increase reliability by more than 50%, and improve operational availability by 45.36 hours per year compared to arrangements without redundancy. Therefore, the proposed approach has the potential to assist manufacturing managers in optimizing resource availability and reliability while maintaining productive capacity.